2013
DOI: 10.1371/journal.pone.0080189
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronicity of Facial Blood Perfusion in Migraine

Abstract: Asymmetrical changes in blood perfusion and asynchronous blood supply to head tissues likely contribute to migraine pathophysiology. Imaging was widely used in order to understand hemodynamic variations in migraine. However, mapping of blood pulsations in the face of migraineurs has not been performed so far. We used the Blood Pulsation Imaging (BPI) technique, which was recently developed in our group, to establish whether 2D-imaging of blood pulsations parameters can reveal new biomarkers of migraine. BPI ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 35 publications
1
44
0
1
Order By: Relevance
“…However, exploring the potential of this developing technique requires a better understanding of the spatially varying phase and pulsating strength that is inherent to mapping PPG signals using the complex inner-product. As a matter of fact, amplitude and phase maps are obtained, but the current published evidence remains insufficient to support the clinical value that these maps may have [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, exploring the potential of this developing technique requires a better understanding of the spatially varying phase and pulsating strength that is inherent to mapping PPG signals using the complex inner-product. As a matter of fact, amplitude and phase maps are obtained, but the current published evidence remains insufficient to support the clinical value that these maps may have [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We proposed recently a PPG imaging of high spatial resolution, called Blood Pulsation Imaging (BPI), which exploits illuminations at the single wavelength [11]. Data processing of digital images in BPI is based on the detection of time-varying modulation of each pixel in the recorded video frames synchronously with the heartbeats [11][12][13][14]. The most important feature of this approach is that, apart from traditional measurement of amplitudes, BPI allows to visualize the distribution of the relative phase of the blood pulsations.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies suggested that migraine was associated with impaired vascular reactivity [37], and characterized by asynchronicity of blood pulsations in the face [18]. PTT estimation with the proposed technique could allow detection of further details of vasomotor reactivity associated with migraine, and even serve a new approach for evaluation efficiency of anti-migraine medicines.…”
Section: Discussionmentioning
confidence: 99%
“…The optical part of the system was similar to that described in our previous work [18]. The IPPG system consisted of a digital black-and-white CMOS camera (8-bit model GigE uEye UI-5220SE of the Imaging Development Systems GmbH) and a lightemitting diode (LED) source for subject's face illumination.…”
Section: Experimental Protocol and Setupmentioning
confidence: 99%
See 1 more Smart Citation